2021
DOI: 10.3390/geriatrics6020038
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Devices for Physical Activity and Healthcare Monitoring in Elderly People: A Critical Review

Abstract: The availability of wearable devices (WDs) to collect biometric information and their use during activities of daily living is significantly increasing in the general population. These small electronic devices, which record fitness and health-related outcomes, have been broadly utilized in industries such as medicine, healthcare, and fitness. Since they are simple to use and progressively cheaper, they have also been used for numerous research purposes. However, despite their increasing popularity, most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 126 publications
1
41
0
1
Order By: Relevance
“…Concerning the attitude towards the technologies, they seem to have good knowledge and skill in the use of computer/smartphone/tablet. Older adults and caregivers agree on the utility of IoT and wearable sensors, in line with other studies [ 26 , 27 , 28 ]. Moreover, most of the participants (in line with previous studies) agree with the primary function of robots and AI to perform care and assistance tasks [ 29 , 30 , 31 ], IoT and wearable sensors to improve self-care [ 26 ], apps and mobile devices to have social opportunities [ 32 ], and virtual/augmented reality to help operators in their work [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…Concerning the attitude towards the technologies, they seem to have good knowledge and skill in the use of computer/smartphone/tablet. Older adults and caregivers agree on the utility of IoT and wearable sensors, in line with other studies [ 26 , 27 , 28 ]. Moreover, most of the participants (in line with previous studies) agree with the primary function of robots and AI to perform care and assistance tasks [ 29 , 30 , 31 ], IoT and wearable sensors to improve self-care [ 26 ], apps and mobile devices to have social opportunities [ 32 ], and virtual/augmented reality to help operators in their work [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have reported slower and low levels of technology adoption and use by older adults, which is primarily fueled by lack of technical skills, negative attitudes or anxiety toward technology, and age-related changes including difficulties with vision, hearing, and fine motor skills. [44][45][46][47] Though technologies such as wearable devices can greatly improve the quality of life for older adults, 48 it is important to make it easier for them to adopt and use these technological devices.…”
Section: Discussionmentioning
confidence: 99%
“…For the evaluation of physical activity, the use of inertial sensors based on accelerometry is common [ 40 ]. These devices can provide, in a simple way, numerous metrics related to physical activity such as the number of steps while walking, the time and intensity of physical activity, study of sedentary lifestyle and the estimation of metabolic expenditure [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consequences are important differences in the results obtained by different devices in the evaluation of the same physical activity [ 42 ]. There is a deficit in the capacity of the devices for their personalization and adaptation to the study of physical activity in people with characteristics different from those used in the validation [ 43 ], which can be a strong source in elderly people because they move slowly and the filters used by the algorithms, if they cannot be customized, can remove the components related to movements and activity [ 40 ]. In addition, in the context of physical therapy and maintenance of the elderly, the prescribed exercises depend on the conditions and characteristics of each patient, so the needs for customization of algorithms and devices is a pending issue in the literature [ 44 ].…”
Section: Discussionmentioning
confidence: 99%